2021
DOI: 10.1088/1361-6560/ac0f2e
|View full text |Cite
|
Sign up to set email alerts
|

The dose response of PTW microDiamond and microSilicon in transverse magnetic field under small field conditions

Abstract: The aim of the present work is to investigate the behavior of two diode-type detectors (PTW microDiamond 60019 and PTW microSilicon 60023) in transverse magnetic field under small field conditions. A formalism based on TRS 483 has been proposed serving as the framework for the application of these high-resolution detectors under these conditions. Measurements were performed at the National Metrology Institute of Germany (PTB, Braunschweig) using a research clinical linear accelerator facility. Quadratic fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…When the output correction factors k were applied, the spread of the corrected values was considerably reduced for the smallest field sizes at 5 cm and 10 cm depth. Moreover, at 0.35 T, Blum et al [ 14 ] found small field output correction factors close to the free magnetic field values for the PTW 60019 and 60023. That’s why, even though the output correction factors were published for measurements without magnetic field at 10 cm depth, they seem to be applicable at low magnetic field at 5 cm depth pending the publication of new MR specific values.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…When the output correction factors k were applied, the spread of the corrected values was considerably reduced for the smallest field sizes at 5 cm and 10 cm depth. Moreover, at 0.35 T, Blum et al [ 14 ] found small field output correction factors close to the free magnetic field values for the PTW 60019 and 60023. That’s why, even though the output correction factors were published for measurements without magnetic field at 10 cm depth, they seem to be applicable at low magnetic field at 5 cm depth pending the publication of new MR specific values.…”
Section: Discussionmentioning
confidence: 70%
“…Generally, diodes are not recommended for output factors (OF) measurements in the presence of a magnetic field [ 13 ]. The diode non-water equivalent density components have been identified as the major contributors to their behaviour in magnetic field and a strong dependence of the small field output correction factors with the magnetic field strength has been found [ 14 ]. Woodings et al compared the PTW 60019 microdiamond detector to a small ionization chamber and they considered it suitable for small field measurements and MR-linac commissioning.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative dosimeters to standard reference ion chambers such as smaller volume chambers [ 72 ], microDiamond and microSilicon type detectors [ 73 ] have also been evaluated. Similar to conventional linacs, the output factors for small fields and the response of detectors under non-equilibrium conditions is an emerging area of research [ 74 ].…”
Section: Future Researchmentioning
confidence: 99%
“…Subsequent measurements were then performed with B=0.35 and 1.4 T without changing the collimator setting in between. More details on the measurement setup can be found in Blum et al (2021). 31021 chamber (middle row) and the microSilicon (lower row).…”
Section: Test Datasetsmentioning
confidence: 99%